Kuttab in Indonesia: Its Existence and Development during the Reform Era - Widiani, Desti; Sirait, Sangkot; Prastowo , Andi; Munip, Abdul (Journal of Al-Tamaddun, 2023)
The re-emergence of the Kuttab is an interesting phenomenon to study in Indonesia. This institution continues to bloom after its last traces in 1952 in Riau. In 2012, the Kuttab Al-Fatih was established and developed in 23 cities. Other kuttabs began to emerge in different Indonesian regions. Therefore, this study attempts to show the existence and development of kuttab in the reform era in Indonesia. Data were collected using a Systematic Literature Review. The results showed that the re-emergence of post-reform kuttab caused a shock effect. This is because the curriculum developed was different from that of Islamic educational institutions. Furthermore, it is necessary to recognize government policy towards kuttab in Indonesia since it has no legal umbrella, hence, a solution is needed to seat this institution. First, the Ministry of Religion/Kemdikbudristek has to make regulations that contain kuttab nomenclature. Second, it is necessary to separate pesantren and kuttab. Third, the kuttab needs to be accommodated, fostered, adopted and supervised. Fourth, this institution is regarded as a formal pathway and is at the SD/MI level. The kuttab has two class systems including the initial I, II, III and the qanuni I, II, III, IV with ages 5-12 years. The kuttab diploma needs to be equivalent to a formal SD/MI education and not only PKBM, MSU, or Package A.